SAT0581-HPR Occupational Challenge or Occupational Balance: Deconstruction of an Occupational Science Concept, Based on Empirical Data of a Qualitative Study in People with Rheumatic Diseases. (23rd January 2014) - Dür, M.; Haider, S.; Binder, A.; Ernst, M.; Smolen, J. S.; Drăgoi, R. G.; Stoffer, M.; Dejaco, C.; Fialka-Moser, V.; Kautzky-Willer, A.; Stamm, T. A.
Abstract : Background: Based on a literature review occupational balance (OB) is defined as the "individual's subjective experience of having the right mix (amount and variation) of occupations in his/her occupational pattern".(1 ) Occupational scientists include other occupations than paid work e.g. self-care, household activities, voluntary work, caring for others.(2 ) Currently there are diverse definitions of OB which are mainly given by occupational therapists.(1 ) Objectives: With this study, we aimed to validate the existing definitions of OB, explore underlying concepts of OB in empirical data of patients with Crohn's disease, rheumatoid arthritis, scleroderma and systemic lupus erythematosus (SLE). Furthermore we wanted to explore its change over life time and disease course. Methods: We conducted a qualitative study using a narrative biographic method asking patients to tell their life stories.(3 ) This approach allows a conceptual analysis of the impact of chronic autoimmune diseases on people's interpretation of their life's experience and biography. Finally we explored the concept OB and its underlying concepts within a long-term perspective over the course of life and disease. Results: 60 patients with a median age of 52 (IQR: 38.75-61.75) years and median disease duration of 10 years (IQR: 8-19) participated and were interviewed on average 2.1 hours. Occupational balance as such, was not found in the data of this study. Instead people's life stories had in common to revolve around occupational challenges. People seek, face and/or meet occupational challenges, seek or face related appreciation, and furthermore use the handling with their occupational challenges to facilitate or inhibit their social connectivity. Furthermore occupational challenges were found to be a flexible concept, changing over different phases of life. Conclusions: Occupational science should focus on occupational challenges instead of OB. The latter concept induces a kind of stability, or a "perfect point of being in balance" which has not been found in the data of this study. Additionally occupational therapists and other health professionals should take into account patients' perspectives and concentrate more on real occupational challenges instead of reaching a conceptualized and idealized state of OB. References: Wagman P, Hakansson C, Bjorklund A. Occupational balance as used in occupational therapy: A concept analysis. Scand. J Occup Ther. 2011. Oechsle M. Work-Life-Balance: Diskurse, Problematiken, Forschungsperspektiven. In: Becker R, Kortendiek B, editors. Handbuch Frauen- und Geschlechterforschung. Theorien, Methoden, Empirie. Wiesbaden: VS Verlag für Sozialwissenschaften, 2008:227-36. Rosenthal G. Reconstruction of Life Stories. Principles of Selection in Generating Stories of Narrative Biographical Interviews. In: Josselson R, Lieblich A, editors. The Narrative Study of Lives. Thousand Oaks: Sage, 1993:59-91. Disclosure of Interest: None Declared